EKSISTENSI KURIKULUM TERSEMBUNYI DALAM PEMBINAAN AKHLAK SISWA DI MADRASAH ALIYAH NEGERI 2 MODEL PADANGSIDIMPUAN - Adek Kholijah; Muksana Pasaribu (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2019)
The background of this research is the neglect of the hidden curriculum, so that the morals of students are not fostered well, and even cause a crisis of faith and morals, even though the existence of a hidden curriculum is very influential on the achievement of educational goals. The research problem is about the Nature of the Hidden Curriculum in Madrasah Aliyah Negeri 2 Padangsidimpuan Model, and the Impact of the Implementation of the Hidden Curriculum in the Moral Development of Students in Madrasah Aliyah Negeri 2 Model Padangsidimpuan. This study aims to describe the Nature of Hidden Curriculum in Madrasah Aliyah Negeri 2 Padangsidimpuan Model, and the Impact of the Implementation of Hidden Curriculum in the Development of Student Morals in Madrasah Aliyah Negeri 2 Model Padangsidimpuan. To achieve this goal, researchers used qualitative data collection techniques by conducting interviews, observations and study documents. The findings of this study indicate that: 1. The nature of the hidden curriculum in Madrasah Aliyah Negeri 2 The Padangsidimpuan model is in the form of activities and habituation such as: accustoming greetings, daily Duha prayer, maintaining cleanliness, fard prayer in congregation, fasting on Monday and Thursday, practicing Monday and giving thursday, holding an honest canteen, syarhil quran, memorizing the surah, carrying out takziah, visiting the sick, disciplining the time, sympathizing people overwritten by calamity, carrying out fardhu kifayah on corpses, full day school, 2. The impact of applying a hidden curriculum in fostering student morals in Madrasah Aliyah Negeri 2 Model Padangsidimpuan, namely: growing awareness and habits of students to perform commendable qualities such as: diligently carrying out fard prayer in congregation, diligently praying duha, diligently reading the Koran memorizing the Koran, diligently fasting Monday and Thursday, fond of practicing charity, caring for others, diligently praying dhuha, diligently reading the Koran memorizing the Koran, diligently fasting Monday and Thursday, fond of practicing charity, caring for others, friendly, honest, patient, polite, polite, orderly, disciplined, responsible answer, love parents, appreciate teachers, love learning, smart, active and creative.Keyword: existence, hidden curriculum and moral development